Decreasing the hydrogen-rich gas circulation ratio and service life extension of the C9-C14 alkanes dehydrogenation catalyst; Chemical Engineering Journal; Vol. 282: The XXI International Conference on Chemical Reactors CHEMREACTOR-21, 15 December 2015, Amsterdam - Frantsina E. V. Evgeniya Vladimirovna; Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Romanovsky R. V. Rostislav Vladimirovich (2015, 2015)
Title screen